Perbedaan Kemampuan Komunikasi Matematis Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Think-Talk-Write (TTW) dan Model Pembelajaran Konvensional Pada Tingkat SMP - Lenny Anggraini Lubis; Wingston Leonard Sihombing (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
This research aims: (1) the mathematical communication abilities of students using the think-talk-write (TTW) cooperative learning model are higher than the mathematical communication abilities of students using conventional learning models in class VIII SMP Negeri 19 Medan, (2) the process of completing answers is created by students in solving problems in the think-talk-write (TTW) cooperative learning model and conventional learning models. This type of research is quantitative research with a Quasi Experimental method. This research was conducted at SMP Negeri 19 Medan. The sampling technique in this research used the Purposive Sampling technique, namely class VIII-5 as a class taught using the think-talk-write type cooperative learning model and class VIII-6 as a class taught with a conventional learning model. The data collection instruments were an observation sheet and a test sheet for students' mathematical communication skills in the form of 4 essay questions. Data analysis in this study used a t-Test with the Independent sample t-Test technique with the help of the SPSS 22 program. The results of the research showed that the average score for the class taught using the think-talk-write cooperative learning model was 80.1 and the class taught with a conventional learning model of 74.6. Hypothesis testing was carried out using the t-test, from the calculation results it was obtained that tcount was 2.501 and ttable 1.67469, the significance level was 0.016<0.05, then H0 was rejected and Ha was accepted, so it was concluded that students' mathematical communication skills used the cooperative learning model type. think-talk-write is higher than students' mathematical communication skills using conventional learning models. Based on the analysis of the process of students' answers to the mathematical communication skills test, students who received think-talk-write cooperative learning were better than students who received conventional learning.